Omissões na interpretação: um estudo de caso das lives no contexto pandêmico - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2022)
This study is justified by the relevance of the ILS' work in guaranteeing the rights of the Deaf Community, understanding the complexity of musical artistic interpretation and the need for studies on this multiple and challenging work. This article aimed to identify and analyze types of omissions in a Portuguese/Libras interpretation in a live musical and we discussed their characteristics and possible reasons. Its theoretical basis is based on Barbosa (2014), Sekeff (2007), Bassnett (2003), Rigo (2019) and Santana (2019). The methodological approach adopted was qualitative with a reflective and analytical analysis. The data point to omissions of some linguistic and extralinguistic aspects based on Rigo (2019), thus, in the process of simultaneous interpretation there are factors directly linked to the development of the interpretive event, among them, the information that emanates from the LF to the AL that are not interpreted that affect the interpretation.
Keywords: Língua Brasileira de Sinais; Interpretação musical; Comunidade surda; Acessibilidade; CNPQ::LINGUISTICA, LETRAS E ARTES::LETRAS; ODS 10 – Redução das desigualdades; ODS 4 – Educação de qualidade